2015
DOI: 10.1159/000381989
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Intravaginal Estriol and Pelvic Floor Rehabilitation in Post-Menopausal Stress Urinary Incontinence

Abstract: Introduction: Pelvic floor muscle training (PFMT) and electrical stimulation (ES) are conservative models of therapy for treating female stress urinary incontinence (SUI). The presence of estradiol receptors in the lower urinary tract advances the case for estradiol therapy in SUI. The aim of our study was to investigate the effects of the combination of pelvic floor rehabilitation and intravaginal estriol (IE) on SUI treatment in postmenopausal women. Material and Methods: Sixty-two women with SUI were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Previous researchers pointed out that the prevalence of UI increased with aging [15] . This increase may be explained with the changes in physical status by aging and age-associated factors including, menopause, comorbidities, increased drug use, and parity [1] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researchers pointed out that the prevalence of UI increased with aging [15] . This increase may be explained with the changes in physical status by aging and age-associated factors including, menopause, comorbidities, increased drug use, and parity [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Parity is the one of the most important risk factors of UI and several previous studies reported that increasing parity was associated with increased risk of UI [13,15,25] . The effect of parity on UI may be related to the development of pelvic muscle atrophy and the impairment in the pelvic muscle nerves during birth [13,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Hot flash was a risk factors for SI. Generally, the lack of estrogen is a risk factor for SI, and estrogen-therapy is an accepted treatment [24]. Therefore, it is acceptable to consider hot flash as a main sign of lack of estrogen and among predictors of SI.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the RCT that evaluated the efficacy of electrical stimulation in the management of stress UI are conflicting [24,28,30]. Consequently, there is a need to conduct more RCT with adequate sample sizes and the use of sensitive, reproducible, and valid outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…A RCT by Castellani et al compared the relative effectiveness of the combination of PHT (PCET, electrical stimulation, and EMG biofeedback) with medication (intravaginal estriol) to treat the stress UI of postmenopausal women [28]. Sixty-two women diagnosed with the disorder were allocated randomly into two groups.…”
Section: Urinary and Fecal (Anal) Incontinencementioning
confidence: 99%